Methicillin-Resistant Staphylococcus aureus: The Magnitude and Risk Factors among Patients Admitted to Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia - Tewodros Tamire; Temesgen Eticha; Temesgen Bati Gelgelu (International Journal of Microbiology)
Background. In healthcare facilities, a gradual increase in methicillin-resistant Staphylococcus aureus (MRSA) infections has been seen over the past 2 decades. Similarly, it has been responsible for the most frequent and invasive pathogens associated with admitted patient infection. Currently, it is considered an urgent threat to public health and classified as one of the top-priority antimicrobial-resistant pathogens. This study aimed to determine the magnitude and associated risk factors of MRSA infection among admitted patients. Methods. A facility-based cross-sectional examination was led on 413 patients admitted to Tikur Anbessa Specialized Hospital from January 2018 to January 2019. A convenient sampling technique was used. Clinical specimens of pus and blood were collected from admitted patients who developed the infection after 48 hours of admission. Gram stain, culture media preparations, and biochemical tests were conducted to identify and isolate the causative agent. Staphylococcus aureus (S. aureus) were identified as MRSA strains after having a zone of inhibition less than or equal to 21 mm to the cefoxitin (30 ug) disc. Bivariate and multivariable logistic regression analyses were computed. The odds ratio, along with 95% CI, was estimated to identify associated risk factors for MRSA infection. Results. Out of 413 collected specimens, 38.7% had coagulase-positive S. aureus of which 35.6% (95% CI: 28.2%–43.0%) were MRSA. Being within the age group of 19–29 years and 30–39 years with AOR = 5.02 and 95% CI: 1.24–20.35 and AOR = 6.65 and 95% CI: 1.78–24.78, respectively, admitting in the hematology ward and the pediatric ward with AOR = 7.80 and 95% CI: 1.82–33.49 and AOR = 10.54 and 95% CI: 1.78–62.42, respectively, and experiencing poor prognosis with AOR = 10.97 and 95% CI: 4.57–26.36 were significantly associated with MRSA infection. Conclusion and Recommendation. The significant magnitude of MRSA was found among patients admitted to this hospital. Therefore, identified risk factors should be considered when executing hospital-acquired infection prevention programs. We also suggest that healthcare providers should consider the identified risk factors while prescribing the antibiotic.